PERAN BRAND LOVE MEMEDIASI PENGARUH BRAND IMAGE TERHADAP WORD OF MOUTH - I Gusti Ayu Ketut Giantari; I Putu Hari Budi Utama; Ni Luh Diah Ayu Wardani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
This study aims to explain the role of brand love in mediating the brand image of WOM (word of mouth). The sample size of 90 people taken using non-probability sampling method is purposive sampling. Data were collected using survey and questionnaire methods. The analysis technique used is path analysis with the help of SPSS 22. The results show that brand love is not able to mediate the influence of brand image on WOM. H & M should be able to maintain the brand image by making update in the design of clothing.